(untitled) (Research, Society and Development, 2020)
The article aims to build a bibliographic review on medicinal plants used in the treatment of gastrointestinal disorders, survey the list of plants found in the literature and verify the existence of studies on the toxicity profile of the main plants found; as well as to identify the main phytochemical compounds of the same. It is an integrative review (IR), which used the following databases for research: PUBMED and SCIELO; works found in the period 2015-2020 were used and the search itself took place between March and April 2020. It is possible to observe the application of different plant species for the treatment of the most varied problems related to the gastrointestinal tract, such as gastritis, diarrhea, stomach pain, colic, constipation. There are scientific gaps on the subject, as from the studies found, there is a lack of presence of health professionals in works that are related to the use of medicinal plants and the need for more research related to the effectiveness and safety of using these products. More research is needed related to the efficacy and safety of medicinal plants used for the treatment of gastrointestinal disorders, so that this knowledge in the literature is strengthened and it becomes part of the professionals’ daily lives.